Let’s Give Dentures Another Chance! - Maskey, B; Shrestha, J (Journal of Nepalese Prosthodontic Society, 2020)
In a complete denture patient, the supporting tissues and the prosthesis are vulnerable to time-dependent changes. The need for maintenance to keep pace with these changes necessitates a regular follow up. However, in a developing country like ours, it is not unusual to find patients either delaying or completely avoiding these follow ups citing various reasons. Often, a new prosthesis is recommended in these situations without considering the prospect of relining and rebasing. This clinical report presents a scenario where one of these maintenance therapies was undertaken to improve the fit and function of the complete denture.